From macroeconomic stability to welfare: Optimizing fiscal rules in commodity-dependent economies - Rodrigo Heresi; Daniela Villacreces Villacis (Inter-American Development Bank (IDB), 2023)
We study the welfare and macroeconomic implications of simple and implementable fiscal policy rules in commodity-dependent economies, where a large share of output, exports, and government revenues depend on exogenous and volatile commodity prices. Using a multi-sector New Keynesian model estimated for the Chilean economy, we find that the welfare-maximizing fiscal policy involves an actively countercyclical response to the tax revenue cycle. In contrast, the optimized response to the commodity revenue cycle is procyclical, given the high persistence and the economic dynamics induced by international commodity price shocks. The optimized fiscal rules deliver significant welfare gains of 0.52% of lifetime consumption for non-Ricardian consumers and 0.06% for Ricardian consumers relative to a benchmark acyclical policy. Lump-sum social transfers are the best instrument to implement the fiscal rule, yielding higher welfare gains, enabling reductions in macroeconomic volatility, and producing only moderate additional volatility in government spending.
Keywords: E62; Q32; F41; 330; Fiscal rules; Raw materials sector; Open economy macroeconomics